COLLABORATION OF TRADITION AND INNOVATION: CURRICULUM DEVELOPMENT AT NURUL JADID ISLAMIC BOARDING SCHOOL - Arifin, Misbahul; Fitriyah, Wiwin; Eka Pradani, Rizki Febri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Nurul Jadid Islamic Boarding School has long been known as an Islamic educational institution that is strong in maintaining the tradition of classical Islamic knowledge. However, in this modern era, the challenges of globalization, digitalization, and the need for 21st-century competencies force Islamic boarding schools to adapt without losing their identity. This study examines how Nurul Jadid Islamic Boarding School develops its curriculum by integrating Islamic traditions with educational innovation. The research method used is a case study with a qualitative approach through in-depth interviews with Islamic boarding school caretakers, teachers, and students and analysis of curriculum documents. The study results show that the Islamic boarding school has succeeded in combining tradition and innovation by applying digital technology in learning, strengthening general subjects, and preserving the study of yellow books. This collaboration creates an education system that maintains Islamic values and prepares students to face the challenges of the modern world. Further research can be conducted to explore the long-term impact of this integration on the academic and spiritual success of students after graduating from the Islamic boarding school as an effort to prepare alums as agents of change who are responsible for creating welfare in society.